COMPARATIVE STUDIES BETWEEN REVERSE PHASE AND MIX MODE CHROMATOGRAPHY TOWARDS SIMULTANEOUS ESTIMATION OF SELECTED ANTIDIABETIC DRUGS (Cuestiones de Fisioterapia, 2024)
This study compares reverse-phase chromatography (RPC) and mixed-mode chromatography (MMC) for the simultaneous estimation of lobeglitazone, pioglitazone, and metformin in human plasma. Analytical challenges associated with the diverse physicochemical properties of these drugs-specifically the extreme hydrophilicity of metformin and moderate polarity of pioglitazone and lobeglitazone-were addressed using protein precipitation and solid-phase extraction techniques